Chapter 19 Italian Sign Language - Geraci, Carlo (De Gruyter, 2015)
Sign Languages of the World is a one-of-a-kind handbook covering 38 of the world's deaf sign languages and auxiliary sign languages. Each sign language has a dedicated chapter, written by experts for the volume. The book includes contributions from both deaf and hearing scholars.